Investigating candidate genes identified by genome-wide studies of granulomatous diseases in susceptibility to tuberculosis: ANXA11 and the CADM family - Salie, Muneeb (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScMedSc (Biomedical Sciences))--University of Stellenbosch, 2010.